The Association between Macroeconomic Uncertainty and Analysts' Forecast Accuracy - Hope, Ole-Kristian (Institutional Knowledge at Singapore Management University, 2005)
This study examines whether macroeconomic uncertainty affects the forecast accuracy of financial analysts in an international setting. We use inflation and foreign exchange volatility as measures of macroeconomic uncertainty. We find strong evidence that forecast accuracy decreases in the level of macroeconomic uncertainty. Further, we document that the negative association between forecast accuracy and macroeconomic variables is more pronounced for emerging economies than developed economies. Overall our results suggest that macroeconomic uncertainty represents a unique dimension in the complexities associated with predicting future firm performance. [PUBLICATION ABSTRACT]